The Effect of Emotional Intelligence and Spiritual Intelligence on Nurses Caring Behaviours with The Leadership Style Over Intervening Variable - Yuni Asmi; Rokiah Kusumapradja; Wahyuni Dian Purwati (Journal of Multidisciplinary Academic, 2020)
Nurses are required to always provide good nursing care to their patients. In this case, the nurse must show a caring attitude, establish a trusting relationship, be sensitive to feelings a patient, and care for all patients sincerely, where these attitudes are included in the nurse's caring behaviour. But in reality, there are still many nurses who have not been able to apply caring behaviour when carrying out nursing care. One of the factors that can influence caring behaviour is emotional intelligence, spiritual intelligence, and effective communication which is certainly influenced by the superior's leadership style. Thus, this study aims to determine the relationship between emotional intelligence and spiritual intelligence, effective communication and leadership style on the caring behaviour of nurses at X Hospital Tangerang. The design of this research is quantitative research. Sampling was done using a total sampling method where the sample consisted of 33 nurses. The data obtained were processed using the Path statistical test (path analysis) of the Amos program. The results showed that there was a significant influence of the emotional intelligence variable on nurses' caring behaviour (p = 0.006). Another finding is that there is no influence of spiritual intelligence on nurses' caring behaviour (p = 0.398) as well as effective communication which also has no significant effect on nurse caring behaviour (p = 0.122). However, the results showed that there was a significant influence of leadership style on nurse caring behaviour (p = ***) and effective communication also had a significant effect on nurse caring behaviour (p = 0.016). The findings obtained from this study were that emotional intelligence and spiritual intelligence affect the caring behaviour of nurses where the superior leadership style is the intermediary. With the existence of health workers who have high emotional intelligence and spiritual intelligence, it is hoped that nurses will be formed who have empathy, compassion, are wiser and improve the quality of nursing care so that caring behaviour that can cause comfort in patients can be formed. Leadership style is an intervening variable in this study. This variable connects emotional intelligence and spiritual intelligence and effective communication on nurse caring behaviour. One of the caring behaviours shown by superiors is by being a role model for the nurse in charge, with the hope that nurses can be motivated to apply caring behaviour to patients, moreover Daan Mogot Tangerang Hospital is a hospital with a military nuance. Therefore, by applying caring behaviour which is based on high emotional intelligence, it will provide a special plus for this hospital. The emotional intelligence of a boss is able to make patients and nurses feel comfortable with their attitude in leading and directing.